Pesantren sebagai Agen Sinkronisasi Hukum Islam dan Hukum Negara: Telaah atas Pondok Pesantren Tebuireng dan Gontor - Syahrudin; Isa, Khairunesa (Pro Justicia: Jurnal Hukum dan Sosial, 2025)
This study aims to analyze the contribution of pesantren (Islamic boarding schools) to the contextual and integrative development of Islamic law in Indonesia, with a particular focus on two major institutions: Pondok Pesantren Tebuireng in Jombang and Pondok Modern Darussalam Gontor in Ponorogo. These pesantren were selected due to their unique characteristics and historical significance in shaping Islamic legal thought in Indonesia. Using a qualitative approach and case study method, the research finds that Tebuireng contributes significantly through its emphasis on progressive and contextual Islamic intellectual traditions, while Gontor excels in producing adaptable Muslim leaders capable of responding to social and legal changes. The findings reveal that the integration of Tebuireng’s intellectual approach and Gontor’s modern, character-based educational system offers a strong model for reconstructing Islamic law in ways that are responsive to contemporary Indonesian society. In conclusion, pesantren have substantial potential to serve as centers for Islamic legal development that are not only normative but also practical, contributing significantly to harmonizing sharia values with the national legal system.